Синдром соединительнотканной дисплазии сердца у детей - Филонова, Т.А.; Савво, В.М. (Таврический медико-биологический вестник, 2013)
Вивчена структура малих аномалій розвитку серця у 240 дітей з ознаками сполучнотканинної дисплазії. Визначено залежність виявлення диспластичних аномалій від віку дитини. Представлені гемодинамічні особливості малого кола кровообігу у дітей з диспластичним серцем. The identified structural features should be also correlated with the age of the child, considering that the many of structural abnormalities of the heart are the dynamic process that requires observation for adequate clinical interpretation and differential approach.